Penyelesaian Sengketa Perdagangan Internasional: Peran World Trade Organization (WTO) - Adela Salsabila; Jihan Rafifah; Najwa Aura F; Enjum Jumhana; Salman Al Farizi Ilham (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
International trade disputes are one of the main challenges in global economic relations. The role of the World Trade Organization (WTO) as a multilateral institution is crucial in providing a fair and efficient dispute settlement mechanism. This article discusses the process of resolving international trade disputes through the WTO, as well as its role and contribution in maintaining stability and fairness in global trade. With a structured dispute settlement mechanism in place, the WTO acts as a guardian of the rules in international trade, preventing larger conflicts and ensuring legal certainty for world trade actors.